Tracked Changes. Extended application of test results for fire resistance and/or smoke control for doorsets, shutter and openable window assemblies, including their elements of building hardware. Fire resistance of hinged and pivoted timber doorsets and openable timber framed windows Part 3, (23rd January 2023) - British Standards Institution,
No abstract available